Expressions of stemness markers in keloid tissue (Medical Journal of Indonesia, 2018)
Background: Keloid is an abnormal wound healing process that extends beyond the site of injury. Keloid and tumor’s shared similarity of recurrence suggesting a shared underlying mechanism that involves stemness. Octamer-binding transcription factor-4 (Oct-4) and aldehyde dehydrogenase-1 (ALDH1) are stem cell stemness markers. This study aimed to analyze Oct-4 and ALDH1 expressions in keloid tissues.Methods: Samples were obtained from keloid tissue excisions from three keloid patients and post-circumcision preputial skin from three healthy donors (normal control) in accordance with the local ethical committee regulation. Total RNA was isolated using TriPure Isolation kit (Ameritech), and expressions of Oct4 and ALDH1 mRNA in keloid and preputial skin were determined by quantitative reverse transcription–polymerase chain reaction (qRT-PCR) using Livak method.Results: The qRT-PCR analysis revealed the expressions of Oct4 and ALDH1 in keloid and preputial skin tissues. Keloid tissues exhibited lower expression levels of Oct-4 and ALDH1 than the preputial skin. The difference was statistically insignificant.Conclusion: Keloid tissues express Oct-4 and ALDH1 as stemness markers, and the stemness characteristics of keloid might be similar to a normal skin.